The importance of sanding in wood finishing processes / Mohd Azhari Abd Aziz - Abd Aziz, Mohd Azhari (2007)
Wood sanding is a first thing that needs to do after the final process to make wood or product. There are the thing that should to do before using the final material of furniture product such as fillers, stains, lacquer and other. The sanding materials are form by mineral substances that process by sand combined with special paper which usually use for wood sanding process. It usually involve the types of abrasive, the right of using grits, ability to handling using the machines and the tools of safety that need to use. All above can be imagine that to get the good quality of surface need to suitable items or material and good skills to increase the quality and value of wood product. Concentration and careful need while manufacturing process can reduce the damage at wood surface. The suitable of sanding operation and develop procedures can increase quality of surface finish. Although, the product can't be produce if someone not wear the safety tools perfectly and rightly. The risk to get the injuries and seriously diseases are highest. Lastly, the suitable of sanding will be increase the excellent or produce the great of product and decrease the holding of handing abrasive tools which to get the risk to injury is highest and produce the product needs more time.